THE USE OF INTERROGATIVE SENTENCES AND ANSWERS TO THEM IN EDUCATIONAL SITUATIONS AT RUSSIAN LANGUAGE LESSONS IN AN UZBEK SCHOOL (American Journal of Research in Humanities and Social Sciences, 2023)
The article deals with the question of the use of interrogative sentences and answers to them in educational situations. For the effective use of question-answer structures in the lessons of the Russian language and literature, it is necessary to consider educational situations from the point of view of the use of interrogative sentences for organizing a lesson.